Međuovisnost razvoja telekomunikacija i turizma - Burmaz, Branimir; Tudor, Branko; Matešić, Ante (Promet - Traffic&Transportation, 2012)
The paper deals with the interdependent quality of development of telecommunications and tourist trade, their relationships and mutual interests. Contribution of telecommunications is felt in the segment of quality of service, structuring and materialization of business policy of travel trade. Of contrast, the actions of demographic, economic, technological and social/cultural forces integrated by the tourist trade exert major impact upon the functioning and development of telecommunications as its infrastructure factor or specific segment. Travel market directly integrated into the international market most timely reacts to the world development trends and thus the development of telecommunications. The indispensable requirement for the introduction of new services shall further be accentuated in respective changes originating from the integration of twelve national markets of the EC into a single common market, while joining it shall prove possible only upon the elimination of technical obstacles to appearing on this market.